Глибоководні дослідження Міжнародної підводно-археологічної експедиції біля південного узбережжя Криму - Воронов, С.О.; Рейда, Р.М.; Вахонєєв, В.В. (Археологічні дослідження в Україні, 2009)
The publication is devoted to the research of the III International Deep-water Expedition in 2008 in the territorial waters of Ukraine to the south from the Crimea. As a result, the group of not known before objects of underwater heri tage has been revealed.